Phyto-mediated polymeric incorporated silver nano-bio-composite for improved dermal complication management: A review - Min He; Jun Hu; Jiaxin Deng; Xueqiang Chen; Anil Kumar Singh; Pooja V. Nagime; Himanshu Paliwal; Sudarshan Singh; Opeyemi Joshua Olatunji (Results in Chemistry)
The intricacies of skin conditions and the limitation of traditional therapeutic strategies make dermal treatment fairly difficult. Recent advancements in nanotechnology field have demonstrated promise in dealing such problems, specifically, the application of biogenic synthesized metallic nano-bio-composites. This review is focused upon synthesis, characterization, and transformation of metallic nanoparticles (NPs) into polymeric composite for the management of dermal complications, with emphasis on how they can enhance drug delivery, promote wound healing, and mitigate inflammation. By employing bioactive-rich substances from plants, the phyto-mediated approach confirms biocompatibility and reduced cytotoxic potential metallic NPs with 99.9 % of antibacterial activity. Such nanocomposites furnish augmented physicochemical properties, including targeted therapeutic action, regulated release, and improved stability, upon combination with polymers and metallic NPs, such as silver nanoparticles (AgNPs). The mechanism responsible for their activity in the treatment of dermal complication due to their excellent antibacterial, antioxidant, and anti-inflammatory activity with a focus on wound healing application have been presented in the paper. Additionally, the review encourages the interdisciplinary strategies to optimize their clinical applicability, while evaluating their current limitations and future research directions. Thus, the review highlights the potential of phyto-mediated polymeric incorporated metallic nano-bio-composites as revolutionizing solution for the management of dermal complications, paving the way for the next-generation therapeutic approaches.